2020
DOI: 10.1016/j.ijnss.2020.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral therapy improves neurocognitive impairment in people living with HIV? A meta-analysis

Abstract: Objectives Although effective antiretroviral therapy (ART) has been used for more than two decades, HIV-associated neurocognitive disorder remains prevalent. Thus, whether ART can improve neurocognitive impairment is controversial. This review aims to explore the effects of ART on cognitive impairment in people living with HIV (PLWH). Methods A systematic literature search was conducted in eight databases (PubMed, Embase, Web of Science, Cochrane Library, CNKI, VIP, Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 64 publications
(103 reference statements)
4
14
0
Order By: Relevance
“…Nadir CD4 was identified as a significant moderator of neurocognitive outcomes with antiretroviral therapy. This agrees with meta-analytic results by Al-khindi et al (2011) and Gao et al (2020) that showed a cognitive benefit of partial immune restoration on ART initiation in participants with advanced HIV infection and low immune status. However, the mean nadir CD4 across studies was low (209 cell/µl; SD = 112.5).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Nadir CD4 was identified as a significant moderator of neurocognitive outcomes with antiretroviral therapy. This agrees with meta-analytic results by Al-khindi et al (2011) and Gao et al (2020) that showed a cognitive benefit of partial immune restoration on ART initiation in participants with advanced HIV infection and low immune status. However, the mean nadir CD4 across studies was low (209 cell/µl; SD = 112.5).…”
Section: Discussionsupporting
confidence: 91%
“…Our evaluation of probable sources of between-study heterogeneity using sub-group analysis identified design-related (between-groups vs. withingroup; cross-sectional vs. longitudinal) and methodological causes (use of normative scores). The subgroup of studies with a pre-and post-ART design showed significantly increased ART impact on cognitive outcomes compared to 2013) and Gao et al (2020). The marked difference in cognitive improvement with ART in cohort studies is most likely due to practice or retest effect due to familiarity with test content or familiarity with test environment and administrative personnel (Collie et al, 2003;Goldberg et al, 2015).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…For cognitive symptoms, the findings are inconclusive regarding whether ART improves or increases cognitive impairment in PWH 40 , 41 . Gao and colleagues conducted a systematic review and found that ART did not improve cognitive function in the population of PWH, especially in PWH in moderate and good physical condition 42 . Paul summarized the neurocognitive phenotype of PWH taking ART and found that PWH had poor understanding and reasoning but no loss of memory after receiving ART 43 .…”
Section: Discussionmentioning
confidence: 99%
“…In the case of ritonavir, it was found that it induces endoplasmic reticulum (ER) stress and mitochondrial outer-membrane permeabilization (MOMP) [ 40 ]. Finally, the data suggesting ART-mediated cognitive performance improvement is still controversial [ 38 , 41 , 42 ]; hence, some studies did not find a beneficial association, while Siangphoe et al [ 42 ] concluded in a meta-analysis that ART actually reduces the risk of developing neuronal disorders such as HAND. Nevertheless, the study did not include in the analysis the type of ART of each patient, which raises a question about if any specific antiretroviral or a combination of them is causing any neurocognitive deficit.…”
Section: Hand and The Long-term Exposure To Artmentioning
confidence: 99%